The Efficacy of Systemic Therapy for Internalizing and Other Disorders of Childhood and Adolescence: A Systematic Review of 38 Randomized Trials. Issue 4 (5th August 2013) - Retzlaff, Ruediger; von, Kirsten; Beher, Stefan; Haun, Markus W.; Schweitzer, Jochen
<x xml:space="preserve">Abstract</x> Systemic therapy (ST) is one of the most widely applied psychotherapeutic approaches in the treatment of children and adolescents, yet few systematic reviews exist on the efficacy of ST with this age group. Parallel to a similar study on adults, a systematic review was performed to analyze the efficacy of ST in the treatment of children and adolescents. All randomized or matched controlled trials (RCT) evaluating ST in any setting with child and adolescent index patients were identified by database searches and cross‐references, as well as in existing meta‐analyses and reviews. Inclusion criteria were: index patient diagnosed with a DSM‐IV or ICD‐10 listed psychological disorder, or suffering from other clinically relevant conditions, and trial published by December 2011. Studies were analyzed according to their sample, research methodology, interventions applied, and results at end‐of‐treatment and at follow‐up. This article presents findings for internalizing and mixed disorders. Thirty‐eight trials were identified, with 33 showing ST to be efficacious for the treatment of internalizing disorders (including mood disorders, eating disorders, and psychological factors in somatic illness). There is some evidence for ST being also efficacious in mixed disorders, anxiety disorders, Asperger disorder, and in cases of child neglect. Results were stable across follow‐up periods of up to 5 years. Trials on the efficacy of ST for externalizing disorders are presented in a second article. There is a sound evidence base for the efficacy of ST as a treatment for internalizing disorders of child and adolescent patients.